Réflexions sur la genèse des Open Badges - Serge Ravet (Centre National d'Enseignement à Distance, 2017)
While many wondered how to recognise informal learning, in 2011, the Open Badges were born at the initiative of the Mozilla and MacArthur foundations. Beyond the opportunity of making informal learning visible, the advent of the Open Badges made it possible to grasp the recognition process of informal learning and to take a critical look at Open Badges through the examination of the technologies developed for their implementation. Thus, the Backpack, developed by the Mozilla Foundation for people to solely store badges issued by others, was criticised for being the literal translation with technologies of the asymmetrical power relationships in favour of institutions.Although it was never explicitly stated, the initial architecture was based on the implicit idea that only an institution has the legitimacy to issue Open Badges; individuals had been denied the right to "recognise".Six years later, after many critical analyses of the technologies and practices developed around Open Badges, notably the realisation that an Open Badge is only a particular form of a claim, a new architecture is now emerging: initially designed to make informal learning visible, Open Badges now offer a way of making informal recognition visible and of valuing it. In this perspective, this text expresses a number of reflections and hypothesis aimed at contributing to the understanding of this phenomenon.